Process of Creation of Awareness and Sensitivity to the Total Environment: Promoting Understanding and Sustainable Management of the Environment (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Environmental Education istherefore the process of creation of awareness and sensitivity to the totalenvironment, acquisition of knowledge, creation of appropriate attitudes andacquisition of skills for solving the environmental problems. The Internationalconference on Environmental Education was held at Tibilisi, U.S.S.R. in 1977.The conference recommended that 'A basic aim of Environmental Education is tosucceed in making individual and communities understand the complex nature ofenvironment and to acquire the knowledge values and attitudes which will helpin the management of quality of environment.